The Influence of Candidate Brand Personality and Islamic Marketing Concepts on Voting Behavior: Evidence from the Lampung Gubernatorial Election - Ujang Mahmud; Finny Ligery; Ahmad Mukhlishin; Muhammad Agus Mushodiq; Subandi (LP2M IAIN Palopo, 2026)
Understanding voting behavior in contemporary local elections requires moving beyond conventional political analysis toward psychological and value-based perspectives. While prior political marketing studies primarily emphasize candidate image and campaign communication, limited research integrates candidate brand personality and Islamic marketing values within a unified framework to explain voter behavior in socio-religious contexts. This study aims to examine the influence of candidate Brand Personality and Political Party Image on voting intention in the Lampung Provincial Gubernatorial Election and to analyze the mediating role of party image. A quantitative explanatory design was employed using survey data collected from 110 millennial voters selected through purposive sampling. Data were analyzed using path analysis to evaluate direct and indirect relationships among variables. The findings indicate that Brand Personality has a positive and significant effect on voting intention, while Political Party Image also significantly influences voting intention. Brand Personality further exerts a strong effect on Political Party Image, confirming a perception transfer mechanism whereby voters generalize evaluations of candidates to the supporting political institution. Political Party Image acts as a partial mediator that strengthens the relationship between candidate personality and voting intention. The structural model demonstrates excellent goodness-of-fit, indicating strong explanatory capability. This study contributes to political marketing literature by introducing an integrative model combining candidate branding and Islamic marketing ethics in explaining local electoral behavior. The findings highlight the strategic importance of aligning candidate personal branding with party identity through consistent, ethical, and value-based political communication to enhance electoral competitiveness.